Exploring the role of students’ perceived EFL teacher support in academic burnout: the mediating effect of academic buoyancy - Xiaoxue Li; Honggang Liu; Miaoyue Xia (Humanities & Social Sciences Communications)
Abstract Despite growing attention on academic burnout as a relatively new concept within language education research, insights into its underlying antecedents in the language learning context remain limited. This research aims to investigate the interplay between students’ academic burnout, academic buoyancy, and perceived teacher support in English-as-a-foreign-language (EFL) learning based on a structural equation modeling (SEM) approach. 603 Chinese upper secondary school students were surveyed to provide data for the analysis. The data was processed using SPSS 26.0 and AMOS 24.0. The SEM analysis underscored that academic burnout was directly alleviated by perceived EFL teacher support and academic buoyancy. Additionally, perceived EFL teacher support indirectly mitigated burnout through the mediation of academic buoyancy. These findings highlight the pivotal role of teacher support and academic buoyancy in mitigating negative burnout emotions. The study’s implications underscore how teacher support and learner buoyancy can effectively manage burnout-related challenges in the EFL learning context, offering significant value for language teaching practice.